Pinocchio: Nearly Practical Verifiable Computation - Parno, Bryan; Howell, Jon; Gentry, Craig; Raykova, Mariana (Proceedings of the IEEE Symposium on Security and Privacy, 2013)
To instill greater confidence in computations outsourced to the cloud, clients should be able to verify the correctness of the results returned. To this end, we introduce Pinocchio, a built system for efficiently verifying general computations while relying only on cryptographic assumptions. With Pinocchio, the client creates a public evaluation key to describe her computation; this setup is proportional to evaluating the computation once. The worker then evaluates the computation on a particular input and uses the evaluation key to produce a proof of correctness. The proof is only 288 bytes, regardless of the computation performed or the size of the inputs and outputs. Anyone can use a public verification key to check the proof. Crucially, our evaluation on seven applications demonstrates that Pinocchio is efficient in practice too. Pinocchio's verification time is typically 10ms: 5-7 orders of magnitude less than previous work; indeed Pinocchio is the first general-purpose system to demonstrate verification cheaper than native execution (for some apps). Pinocchio also reduces the worker's proof effort by an additional 19-60x. As an additional feature, Pinocchio generalizes to zero-knowledge proofs at a negligible cost over the base protocol. Finally, to aid development, Pinocchio provides an end-to-end toolchain that compiles a subset of C into programs that implement the verifiable computation protocol. For the full version of our paper, including a correction to the verification procedure, see http://eprint.iacr.org/2013/279 Pinocchio's source code is also available! Visit https://vc.codeplex.com for more info. Coverage from the MIT Technology Review: http://www.technologyreview.com/news/515081/microsoft-and-ibm-researchers-develop-a-lie-detector-for-the-cloud/
Best Paper Award